EFISIENSI PEMASARAN BAWANG MERAH (KASUS: KABUPATEN BREBES, PROVINSI JAWA TENGAH) - Ivony Annisa; Ratna Winandi Asmarantaka; Rita Nurmalina (Universitas Mercu Buana, 2018)
Abstract. This study aims to analyze the operational efficiency (marketing margin, farmer’s share, profit ratio) and the price efficiency in Brebes Regency. Quatitative data processing used to analyze marketing margin, farmer’s share, the ratio of benefits to costs by using Microsoft Excel 2016 while market integration alaysis used Eviews 9. Qualitative data processing used to analyze marketing channels and marketing istitutions. The research results showed that there are seven types of marketing channels in the marketing system of shallot in Brebes Regency. Analysis of operational efficiency showed marketing channel that relative efficient were channel 6 (farmerdistrict assembler-regency assembler-outside the province wholesaler). Analysis of price efficiency showed that the shallot markets were integrated in short term.